2005
DOI: 10.1038/sj.gene.6364258
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype analysis of the SDF-1 (CXCL12) gene in a longitudinal HIV-1/AIDS cohort study

Abstract: The stromal-derived factor-1 (SDF-1) chemokine gene encodes the only natural ligand for CXCR4, the coreceptor for the pathogenic X4 HIV-1 strains. A single-nucleotide polymorphism (SNP) in the 3 0 untranslated region (SDF1-3 0 A ¼ rs1801157) of SDF-1 was reported to be protective against infection and progression in some, but not other, epidemiological studies. To identify additional alleles that may influence HIV-1 infection and progression to AIDS, nine SNPs (including rs1801157) spanning 20.2 kb in and arou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 56 publications
1
15
2
Order By: Relevance
“…Our result was concordant with those of the reports denying the association, though Modi et al 32 recently reported its protective effect as haplotype.…”
Section: Allelic Frequencysupporting
confidence: 95%
“…Our result was concordant with those of the reports denying the association, though Modi et al 32 recently reported its protective effect as haplotype.…”
Section: Allelic Frequencysupporting
confidence: 95%
“…Until earlier this decade, CXCL12 was thought of mainly as an oncologic and immunologic mediator of disease in humans (Modi et al 2005; Mohle et al 1998; Zou et al 1998). Further, studies have shown that CXCL12 acts on lymphocytes and monocytes in vitro, and strongly attracts mononuclear cells in vivo.…”
Section: Chemokine Structure Function and Molecular Overview Of Cxcl12mentioning
confidence: 99%
“…In line with this, it was demonstrated that the ligand of CCR5 (CCL3/MIP-1a, CCL4/MIP-1b, CCL5/RANTES) and CXCR4 (CXCL12) could effectively block the entry of R5 and X4 strains respectively [243,244]. Moreover, polymorphisms of CCR5 [245] or CXCL12 [246][247][248] that affect expression of the receptor at the cell membrane [245] or stability of the chemokine [249,250], respectively, are associated to resistance or higher susceptibility to HIV infection. Transmission and early progression of HIV infection mostly involve R5 viruses [240,251].…”
Section: Role In Hiv Infectionmentioning
confidence: 51%